THE ROLE OF HOMEWORK IN TEACHING ENGLISH - Muhammedova Inobat Shavkatjonqizi; Qo'chqorova Zulfizar Abduxamidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article explores the role of homework in teaching language, drawing on the perspectives of researchers such as Harris Cooper, Alfie Kohn, Robert Marzano, and John Hattie. While some argue that purposeful and targeted homework assignments can support language learning, others raise concerns about potential negative effects and limited impact on student achievement. The article concludes that the effectiveness of homework in teaching language may depend on how it is used and integrated into a comprehensive approach to language education.